MATHEMATICAL MODELING OF THERMOPHYSICAL PROCESSES IN THERMOELECTRIC DEVICES FOR SEAWATER DESALINATION - T. A. Ismailov; A. M. Gadzhiev; Sh. A. Yusufov (Вестник Дагестанского государственного технического университета: Технические науки)
The article considers the mathematical modeling of thermal processes of phase transition «water-ice» to reflect the changes on the boundary of the impurity concentration, typical for fresh water by the method of freezing sea. The design of the device for producing melt water with the use of thermoelectric converters.